Desarrollo de una aplicación web y móvil para la gestión de inmuebles en el conjunto habitacional los Arupos de Latacunga. - Pacheco Astudillo, Cristian Santiago (2024)
Real estate management has benefited in recent times thanks to several residential complexes, as compiled in previous research mentioned in the background. These studies have shown that the acquisition of systems has benefited residential developments. Based on these findings, this project focuses on developing a web and mobile application using agile practices to optimize real estate management processes in the Los Arupos Residential Complex in Latacunga. Its aim is to improve and streamline tasks such as property management, publishing sales or rentals, scheduling visits through appointments, managing fee payments, and communication between owners. Tools such as CodeIgniter, PHP, MySQL and Java were used, along with the MVC model, and interviews and surveys were conducted to gather user requirements. The XP methodology was used, prioritizing collaboration between the development team and users. The process included analysis, design, development and testing stages. The integration of the application improved accessibility and user experience, representing progress for real estate management in Los Arupos, by providing an efficient and effective platform for process automation and improvement of the user experience.